Benefits and challenges of corporate social responsibility implementations: Evidence from manufacturing sector in Malaysia - Amira Hanim Azman, Nur; Mustapha, Mazlina (International Journal of Engineering and Technology, 2018)
Prior studies posited that corporate social responsibility (CSR) by organizations indicates a continuum business commitment to act appropriately. CSR activities carried out would capture the issues, processes and values that companies must tackle to minimize harmful effects stemming from their activities and at the same time the company can create economic, social as well as environmental value for the society. However, not all companies would be motivated to carry out CSR activities. Thus, this study aims to examine the challenges that companies have to face in implementing CSR activities. In addition, the benefits derived from the activities are also discussed. Questionnaires were distributed to manufacturing companies registered with the Federation of Malaysian Manufacturers. The results of this research project suggest that respondent companies appear to apply stakeholder approach in implementation of their CSR activities, where they value their relationship with the stakeholders and are very concerned about the stakeholdersâ€™ perceptions on their companies. The CSR activities which they implement appear to serve as a bridge to tighten these relationships. On the other hand, the cost and complexity of implementation, and time consumed to implement are among the biggest challenges to the organizations in their implementation of CSR activities.Â Â